Isolasi Jamur Dari Buah Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) Yang Terinfeksi Di Perkebunan Kelapa SawitKubu Raya - Riza Linda, Uvisha Sukma Kalpajar, Siti Khotimah, (Universitas Tanjungpura, 2015)
The difficulties in oil palm cultivation are mostly caused by several symptoms of disease, such as the fruit that is infected with fungi. Fungi generally infect the oil palm trees aged 3-9 years. This research aimed to isolate and identify the fungi from the infected fruit of oil palm at the oil palm plantation of PT. Agroasia Palmdale Kubu Raya. The research was carried out from March to June 2015 at the Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences of Tanjungpura University Pontianak. This research used a direct planting method on the PDA and CYA media. The data obtained will be visually and descriptively displayed. The research findings indicated that there were 4 fungal isolates of the species members of Aspergillus sp.U1, Curvularia sp.U2, Penicillium sp.U3, dan Fusarium sp.U4 that infected the oil palm fruit under the environmental factors namely the temperature of 29-300C, humidity of 80- 85% and pH of 6.2 to 6.4.